2014
DOI: 10.1037/fam0000021
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial to test the efficacy of a family-focused, culturally informed therapy for schizophrenia.

Abstract: Research strongly suggests that family interventions can benefit patients with schizophrenia, yet current interventions often fail to consider the cultural context and spiritual practices that may make them more effective and relevant to ethnic minority populations. We have developed a family focused, culturally informed treatment for schizophrenia (CIT-S) patients and their caregivers to address this gap. Sixty-nine families were randomized to either 15 sessions of CIT-S or to a 3-session psychoeducation (PSY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 56 publications
(68 reference statements)
2
48
0
Order By: Relevance
“…This result is consistent with the results of the studies conducted by Awad et al (2008), Smith and Segal, (2014), Hasan, Callaghan and Lymn (2015), and Weisman de Mamani, Weintraub, Gurak and Maura (2014), which showed that a change in the emotional attitude of patients' relatives (such as labeling, guilt, anger, and being worried about oneself, the patient and the future) has an important role in the effectiveness of family-based psychoeducational programs in the progression of schizophrenia.…”
Section: Discussionsupporting
confidence: 82%
“…This result is consistent with the results of the studies conducted by Awad et al (2008), Smith and Segal, (2014), Hasan, Callaghan and Lymn (2015), and Weisman de Mamani, Weintraub, Gurak and Maura (2014), which showed that a change in the emotional attitude of patients' relatives (such as labeling, guilt, anger, and being worried about oneself, the patient and the future) has an important role in the effectiveness of family-based psychoeducational programs in the progression of schizophrenia.…”
Section: Discussionsupporting
confidence: 82%
“…Results from this intervention study demonstrated that when compared to a psychoeducation only control condition, patients assigned to the CIT-S condition had significantly lower psychiatric symptom severity at treatment termination (while controlling for baseline symptoms; Weisman de Mamani et al, 2014). Furthermore, caregivers in the CIT-S condition also demonstrated reduced levels of caregiver burden at treatment termination in comparison to those in the control condition (Weisman de Mamani & Suro, 2015).…”
Section: Methodsmentioning
confidence: 87%
“…The current study is part of a larger treatment study examining how a family-focused, Culturally Informed Treatment for Schizophrenia (CIT-S) and other psychosocial factors relate to patient and caregiver functioning in individuals diagnosed with schizophrenia and their family members (see Weisman, 2005; Weisman de Mamani et al, 2014 for a more detailed description of the larger project). Results from this intervention study demonstrated that when compared to a psychoeducation only control condition, patients assigned to the CIT-S condition had significantly lower psychiatric symptom severity at treatment termination (while controlling for baseline symptoms; Weisman de Mamani et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…In line with study hypotheses, patients assigned to the CIT‐S condition had significantly less severe psychiatric symptoms at treatment termination than did patients assigned to the psychoeducation condition controlling for baseline symptoms (Weisman de Mamani et al . ). A later study using data from this project also indicated that CIT‐S outperformed a psychoeducation only comparison condition in reducing caregiver burden (Weisman de Mamani & Suro ).…”
Section: Methodsmentioning
confidence: 97%
“…This study is part of a larger project on schizophrenia that examines how a family focused culturally informed treatment and other psychosocial factors relate to functioning in patients diagnosed with schizophrenia and their caregivers (for a detailed description, please see Weisman de Mamani et al 2014b, Weisman de Mamani & Suro 2015. Baseline data were also collected to examine a variety of hypotheses regarding correlates of patient and caregiver distress and burden (Suro & Weisman de Mamani 2013).…”
Section: Methodsmentioning
confidence: 99%